INVESTMENT DECISION INFLUENCE ANALYSIS, FUNDING DECISION, DIVIDEND POLICY PROFITABILITY LEVEL OF VALUE COMPANY (Empirical Study on LQ-45 Companies listed on the Exchange Indonesian Securities Period 2018-2022) - Wahyu Ramadhan; Hadi Samanto; Desy Nur Pratiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to show and analyze the partial effect of investment decisions, funding decisions, dividend policy and profitability on firm value. The purpose of this research is also to provide investment ideas to investors. The population of this study is 45 companies listed on the Indonesia Stock Exchange in the 2017-2021 period to calculate the LQ-45 index. The sample was selected using a targeted sampling technique and 23 companies did not meet predetermined criteria and were therefore excluded from the sample. Data analysis was performed using multiple linear regression analysis. Based on the results of data analysis, it can be concluded that investment decisions have a significant positive effect on value, funding decisions have a significant positive effect on firm value, dividend policy has a significant positive effect on firm value, and profitability has a significant positive effect on firm value. Keywords: company value, investment decision, funding decision, dividend policy, profitab